Evaluation of compliance between the results of Pap smear test and pathological specimens sent to the pathology department of Shaheed Sadoughi hospital in Yazd city in 2011-2014 - Arab Badkobeh, Khadijeh; Sheikhpour, Robab; Moghimi, Mansour (Advances in Nursing & Midwifery, 2018)
Abstract Background and Aim: Pap smear test is the most effective and appropriate screening method for cervical cancer prevention. This technique, due to early detection power in early stage of invasive cancers, causes decreased mortality of cervical cancer. The purpose of this study was to assess the compliance between the results of Pap smear test with biopsy specimens sent to the pathology department of the Shaheed Sadoughi hospital. Materials and Methods: In this cross sectional study, 145 cytology and pathology specimens that was sent to the pathology department of the Shaheed Sadoughi hospital were selected. Agreement between the result of cytology test and pathology was analyzed with statistical software SPSS and kappa agreement test. P<0.01 was considered statistically significant. Results: The result of cytology and pathology showed that there is a little agreement between cytology and pathology results (P<0.01, K: 0.26). Conclusion: According to the results, low levels of agreement was observed between the result of pop smear test and pathology results. Therefore to promote quality of cytological reports, the improvement of performance of midwives, cytologist and resident are recommended. Key words: Uterine cancer; Pap-smear; Biopsy